(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This research was conducted in Al-Qalouf during 2017 and 2018 on Loquat trees of 12 years old of the cultivars "Al-koumathry" and "Al-Toufahi" in order to study the effect of the flower-thinning on the percentage of the fruit-set and quality fruits. The results showed: - The process of thinning flowers by 75% of the flowers of the inflorescence raised the percentage of the fruit-set significantly from 9.17% in the control to 23.49%, followed by the treatment of the 50% dilution with (16.17) in the variety Al-koumathry, and from 9.72% in the control to 25.09% in the Al-Toufahi, variety, followed by a 50% thinning treatment (19.36%). The results also showed that the process of flower thinning increased the average weight of the fruit significantly, as it reached 41.93 g and 36.30 g in the both treatments, by 75% and 50%, respectively, while did not exceed 31.28 g in the control in the Al-koumathry variety, and in the "Al-Toufahi" variety increased average fruit weight from 19.05 g in a control to 28.50 g and 24.50 g in both thinning processes of 75% and 50%, respectively, where the differences were significant. - The percentage of clearing reached 88.58% in the Al-koumathry variety, and 79.22% in the Al-Toufahi variety when the 75% of the flowers thinning, followed by the treatment of the thinning of 50% of the flowers of the inflorescence of the flowers, as the percentage eaten part reached 86.30% and 76.31% in both cultivars, respectively, while did not exceed 82.83% and 70.73% in the control. - Reducing the flowerthinning process improved the percentage of total dissolved solids in the fruits resulted and ranged between 12.62% and 11.30% in the treatment of floer-thinning for 75% of flowers and control, respectively in the variety Al-koumathry, and between 13.48% when 75% of flowers thinning and 12.22% in the control of the Al-Toufahi variety.